THE IMPACT OF EXTENDED RETIREMENT AGE ON SAVINGS AMONG MALAYSIAN GOVERNMENT EMPLOYEES: AN EMPIRICAL STUDY - Sheikh Abdul Mutalib, Siti Khairunnisa; Md Ahmad Ridzuan, Ahmad Nur Azam; Mohd Helmi, Mohd Firdaus (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This research examines the implications of increasing the retirement age for government workers in Malaysia, focusing on its effects on savings behaviour, pension sustainability, and economic participation. Drawing from national labour statistics, Employees Provident Fund (EPF) reports, and World Bank recommendations, the study identifies both the potential benefits and drawbacks of such a policy shift. While extending the retirement age can enhance retirement savings, maintain a larger labour force, and ease pension pressures, it also raises challenges such as age discrimination, reduced job opportunities for younger workers, and possible health-related work limitations. The study recommends a phased retirement age increase, improved retirement savings schemes, enhanced financial literacy programs, and flexible employment options. These strategies aim to balance economic sustainability with social equity for Malaysia’s ageing workforce.